Study of the Covid-19 related quarantine concept as an emerging category of a linguistic consciousness - Віталій Шимко; Анжела Бабаджанова (Психолінгвістика, 2020)
Objective. Study of the Covid-19 related quarantine concept as an emerging category of linguistic consciousness of Ukrainians.